Implementation of the Child Protection Policy through Pentahelix Collaboration in West Sumatra Province - Lestari, Sri Fuji; Irwan, Irwan; Elvawato, Elvawati (PT Inovasi Pratama Internasional, 2025)
The implementation of Law No. 35/2014 on Child Protection provides a legal framework to protect children from various forms of violence, including sexual violence. Nevertheless, there are still challenges in its implementation. According to the records of the Office of Women's Empowerment and Child Protection, Population Control and Family Planning (DP3AP2KB) of West Sumatra Province, compiled from the information system on the protection of women and children has increased in the last 5 (five) years. This research aims to analyze the actors involved in the implementation of child protection in West Sumatra Province with data collection methods of documentation studies, interviews and FGDs, then the data is processed using a qualitative approach and a quantitative approach or known as a mixed approach. The approach uses the Miles and Huberman model and the mactor application. The theory used Advocacy Coalition Framework (ACF) and Pentahelix theory are two approaches that can complement each other in analyzing public policy. Meanwhile, Pentahelix emphasizes collaboration between five main actors: government, community, academia, business, and media. Combining these two theories can provide a deeper understanding of policy dynamics. The implementation of child protection policy implementation through pentahelik collaboration in factor analysis can be concluded that the actor who has a major influence is the government because the government is the actor who is in direct contact both in practical and policy aspects, all actors provide positive support, although the business world has not shown a collaborative relationship in the implementation of child protection, the government has the power to influence other actors, community/community collaboration is not strong enough to influence implementation.